Barefoot running improves economy at high intensities and peak treadmill velocity - Reeves, K. A.; Corbett, J.; Barwood, M. J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Barefoot running can improve running economy (RE) compared to shod running at low exercise intensities, but data is lacking for the higher intensities typical during many distance running competitions. The influence of barefoot running on the velocity at maximal oxygen uptake (vVO2max) and peak incremental treadmill test velocity (vmax) is unknown. The present study tested the hypotheses that barefoot running would improve RE, vVO2max and vmax relative to shod running.